2015
DOI: 10.1111/tpj.13097
|View full text |Cite
|
Sign up to set email alerts
|

The cytokinin response factors modulate root and shoot growth and promote leaf senescence in Arabidopsis

Abstract: SUMMARYThe cytokinin response factors (CRFs) are a group of related AP2/ERF transcription factors that are transcriptionally induced by cytokinin. Here we explore the role of the CRFs in Arabidopsis thaliana growth and development by analyzing lines with decreased and increased CRF function. While single crf mutations have no appreciable phenotypes, disruption of multiple CRFs results in larger rosettes, delayed leaf senescence, a smaller root apical meristem (RAM), reduced primary and lateral root growth, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 85 publications
4
84
1
1
Order By: Relevance
“…crf1,3,5,6 quadruple mutants displayed strong inhibition of primary root elongation compared with that of the wild type (Raines et al, 2016). LR numbers of both crf2,5,6 and crf3,5,6 triple mutants were reduced compared with the wild type (Raines et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…crf1,3,5,6 quadruple mutants displayed strong inhibition of primary root elongation compared with that of the wild type (Raines et al, 2016). LR numbers of both crf2,5,6 and crf3,5,6 triple mutants were reduced compared with the wild type (Raines et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Loss-offunction mutations in CRF2 or CRF3 or both CRF3 and CRF6 or CRF2, CRF3, and CRF6 caused reductions in root length, root meristem size, and LRP density, whereas overexpression of CRF2 or CRF3 or CRF6 enhanced LRP density ( Simá sková et al, 2015). In addition, multiple mutations in CRFs result in larger rosettes, delayed leaf senescence, and shorter hypocotyls in etiolated seedlings (Raines et al, 2016). These recent studies along with our present results indicate that the CRF genes play roles in regulating multiple aspects of plant growth and development including root system architecture and plant response to cold and freezing stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the influence of auxin on the cell cycle is still fragmentary, but primary evidence indicates that auxin acts on several targets involved in the control of cell cycle (PerrotRechenmann, 2010). On the other hand, the ability of CKs to promote cell division, in particular through their action on D-type cyclins, was described several years ago (Dewitte et al, 2007;RiouKhamlichi et al, 1999), and it has been recently been shown that the transcript levels of several cell cycle-related genes were decreased in roots of the crf1,3,5,6 quadruple mutant (Raines et al, 2016).…”
Section: Pcre1 Is Required For Pistil Development and Ovule Primordiamentioning
confidence: 99%
“…Posttranslational modification was necessary to activate this phosphorylation site (Dubouzet et al, 2003;Liu et al, 1998). Phosphorylation regulation via histidine kinases has also been suggested for the ERF-VI (Raines et al, 2016). Another ERF belonging to the subgroup of ERF-IXb, AtERF104 required an interaction with the mitogen-activated protein kinase 6 (MPK6) for its stability (Bethke et al, 2009).…”
Section: Potential Post-transcriptional and Posttranslational Regulatmentioning
confidence: 99%